Performance evaluation of enhanced-TCP in wireless IPv6 network - Yew, Been Seok (School of Computer and Communication Engineering, 2013)
This research focuses on enhancing the performance of TCP by implementing the TCP congestion control algorithm in a wireless IPv6 network.